ANALISIS KEPUASAN PENGGUNAAN SISTEM INFORMASI PERKREDITAN (STUDI KASUS: KOPERASI PERUMAHAN WANABAKTI NUSANTARA) - M. Fajriyansyah S.; Edi Abdurachman (Bina Nusantara University, 2012)
In the dynamic aviation business, change is a difficult thing to avoid, especially when it comes to the use of information technology. However, when information technology has been used, many problems can emerge and it is important to comply with the needs and expectations of management, as the company has often allocated large budgets for development. The users also need to know whether it meets their expectations or not. Measurements will be performed by comparing the independent variables of Informativeness, Information Format, Ease of Use, Timeliness and Reliability, as well as user aspects divided into a wide variety of factors, namely Age, Work Experience, , Background Department of Education, Training, and Old Computer Usage. Analysis was conducted on the gap analysis, linear regression analysis, and chi-square analysis. From the analyses there was found to be a significant gap between performance and user expectations in the KPWN credit information system. The regression analysis found that the only variable significantly related to user satisfaction was Reliability, and the chi-square analysis found that Educational Background significantly influenced user satisfaction.